Wind nebulae and supernova remnants of very massive stars. Issue 3 (26th February 2020) - Meyer, D M-A; Petrov, M; Pohl, M
ABSTRACT: A very small fraction of (runaway) massive stars have masses exceeding $60\!-\!70\, \rm M_{\odot }$ and are predicted to evolve as luminous blue variable and Wolf–Rayet stars before ending their lives as core-collapse supernovae. Our 2D axisymmetric hydrodynamical simulations explore how a fast wind ($2000\, \rm km\, \rm s^{-1}$ ) and high mass-loss rate ($10^{-5}\, \rm M_{\odot }\, \rm yr^{-1}$ ) can impact the morphology of the circumstellar medium. It is shaped as 100 pc-scale wind nebula that can be pierced by the driving star when it supersonically moves with velocity $20\!-\!40\, \rm km\, \rm s^{-1}$ through the interstellar medium (ISM) in the Galactic plane. The motion of such runaway stars displaces the position of the supernova explosion out of their bow shock nebula, imposing asymmetries to the eventual shock wave expansion and engendering Cygnus-loop-like supernova remnants. We conclude that the size (up to more than $200\, \rm pc$ ) of the filamentary wind cavity in which the chemically enriched supernova ejecta expand, mixing efficiently the wind and ISM materials by at least $10{{\ \rm per\ cent}}$ in number density, can be used as a tracer of the runaway nature of the very massive progenitors of such $0.1\, \rm Myr$ old remnants. Our results motivate further observational campaigns devoted to the bow shock of the very massive stars BD+43°3654 and to the close surroundings of the synchrotron-emitting Wolf–Rayet shell G2.4+1.4.